HUBUNGAN ANTARA PERUBAHAN KEDALAMAN KURVA VON SPEE DENGAN PERUBAHAN TINGGI WAJAH ANTERIOR BAWAH DAN SUDUT BIDANG MANDIBULA PADA PERAWATAN DEEP BITE (Kajian Sefalogram Lateral Pada Perawatan Maloklusi Kelas I Angle Dengan Pencabutan Empat Gigi Premolar Pertama Menggunakan Teknik Begg) - , Vega Mandala; , drg. Cendrawasih, AF, M.Kes Ort (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Deep bite is often associated with excessive curve of Spee depth. Lower anterior facial height is an aspect considered in deep bite treatment. This height is correlated with mandibular plane angle. The objective of this study is to determine the relationship between changes of the curve of Spee depth and changes of lower anterior facial height and mandibular plane angle in deep bite treatment using Begg technique. This research was based on evaluation of 15 pre and post treatment cephalograms with following criterias Class I Angle malocclusion, 18 to 30 years old subjects, deep bite with 4 first premolar extraction. Cephalogram measurement was done on curve of Spee depth, ANS-menton distance, and SN-GoGn angle. Regression analysis was done on pre and post treatment measurement changes. The result showed that curve of Spee depth was decreased 2,10Â±0,73 mm while lower anterior facial height was increased 1,75Â±1,5 mm and mandibular plane angle was increased 1,23Â±1,32Ë after treatment and there were no significant relationship between changes of curve of Spee depth with lower anterior facial height and mandibular plane angle (p>0,05). It can be concluded that changes in curve of Spee depth was not correlated either with the changes of the lower anterior facial height or the mandibular plane angle